Ibuprofen and indomethacin for the closure of the patent ductus arteriosus - Pacifici,Gian Maria (2016)
The ductus arteriosus connects the pulmonary artery with the aorta and allows right ventricular blood to bypass the unexpanded lungs. In mature infants, the ductus arteriosus closes after birth. Patent ductus arteriosus occurs in 70% of preterm infants with a birth weight < 1,000 grams. Failure of the ductus arteriosus to close has been associated with intraventricular hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia, periventricular leukomalacia, renal failure, and persistent pulmonary hypertension. The drugs used to treat the patent ductus arteriosus are ibuprofen and indomethacin which are potent non-selective inhibitors of cyclo-oxygenase (COX) and therefore inhibit prostaglandin E2 synthesis. Prostaglandin E2 relaxes smooth muscle and tends to inhibit the closure of the patent ductus arteriosus. Intravenous ibuprofen and indomethacin inhibit prostaglandin E2 synthesis and thereby close the patent ductus arteriosus with similar efficacy. Indomethacin reduces the blood flow velocity in kidneys, intestine and brain. Ibuprofen has less effect on blood flow velocity in these organs. There is a significant increase in serum creatinine after indomethacin administration but not after ibuprofen and infants treated with ibuprofen have higher creatinine clearance. Oliguria (urine output < 1 ml/kg/h) occurs more frequently with indomethacin than with ibuprofen. Indomethacin requires furosemide for urine output more often than ibuprofen. Ibuprofen reduces the risk of necrotizing enterocolitis and transient renal insufficiency and it is the drug of choice for closing the patent ductus arteriosus. Ibuprofen and indomethacin may be administered orally. In conclusion, intravenous ibuprofen and indomethacin close the patent ductus arteriosus at the same rate, but indomethacin is more toxic than ibuprofen.